Determination of Applicable Adjacent Horizontal Curve Radii Using Operating Speed - Cvitanić, Dražen; Maljković, Biljana (Promet - Traffic&Transportation, 2019)
Design of curves and their adjacent elements presents the greatest safety problem on rural two-lane roads. The use of the existing alignment consistency safety criteria (design, operating speed, and driving dynamic consistency) could have some shortcomings, especially in countries where the project or design speed is in use instead of (higher) operating speed. The consequence is that the designer should use smaller cross fall on curves than needed, while the calculated side friction is lower than in reality. Further, the existing graphs of adjacent curve radii do not take into account that there is a maximum operating speed achieved for a certain radius or long tangent above which it does not increase. This paper presents a methodology for determination of adjacent horizontal curve radii, with and without tangent between, based on the operating speed models which include dependence of operating speeds on tangents and curves on speed of adjacent alignment elements as well as maximum tangent and curve speed. The developed graphs of adjacent radii at the same time include the limiting values of driving dynamic consistency criteria, so the road designer does not need to calculate permissible and demand side friction for every combination of adjacent alignment elements.